The Value of Integrating Laser Scanning and Photogrammetry to Overcome Standalone Techniques Limitations - A Review Study - Al-Saedi, Ali Salah J.; Abed, Fanar M.; Alwan, Imzahim A. (Iraqi Journal of Science, 2025)
Laser scanning and photogrammetry are two revolutionary technologies garnering an increasing interest in various engineering and construction fields. These technologies offer outstanding benefits, including non-contact remote sensing activities and highly automated and effective large-scale sampling capability that attracts more attention. New developments in remote sensing standalone methods, including range-based and image-based modeling (e.g., Terrestrial Laser Scanning and Structure from Motion- Multi-View Stereo photogrammetry), produce 3D geometrically and physical data that is more exhaustive, precise, and accurate than ever. However, neither standalone technique can offer higher-quality results than the other due to sensor limitations and shortcomings in certain conditions. On the contrary, integrating multiple techniques can help overcome the single sensor's limitation and allow complete 3D realism data outcomes that better facilitate post-processing, such as object classification and segmentation. Combining multiple RS datasets has recently obtained much attention in the Geomatics research community that has been widespread lately. To highlight the available integration and combination of laser scanning and photogrammetry approaches, this study reviews the various up-to-date approaches currently in use towards 3D realism products, both in geometric and physical aspects. This work aims to give a systematic review that depends on qualitative and scientometric analysis to describe the progress and current state-of-the-art topic. The review also brings out future research endeavors to pave the road for different studies in diverse applications. Efforts also highlight the issues arising from individual and integrated image- and range-based modeling utilization. This includes discussing the most effective methods for gathering high-resolution 3D spatial information from combination approaches.